CHLORINE ISOTOPE VAPOR-LIQUID FRACTIONATION DURING EXPERIMENTAL FLUID-PHASE SEPARATION AT 400 °C/23 MPA TO 450 °C/42 MPA - Liebscher A.; Barnes J.; Sharp Z. (My University, 2006)
We measured experimentally the chlorine isotope fractionation between coexisting vapor and liquid in the system H2O-NaCl. Experiments were performed between 23 and 28 MPa along the 400 °C isotherm and between 38 and 42 MPa along the 450 °C isotherm. Calculated chlorine isotope fractionation Δ37Clvapor-liquid = δ37Clvapor - δ37Clliquid (1σ = ± 0.17‰) between coexisting vapor and liquid are generally within 0.2‰ of 0, although there is a trend at both 400 °C and 450 °C in which the Δ37Clvapor-liquid values change with pressure beyond statistical uncertainty as follows:{A table is presented}. This trend is supported by earlier work of Magenheim [A.J. Magenheim, 1995. Oceanic borehole fluid chemistry and analysis of chlorine stable isotopes in silicate rocks. PhD Thesis, University of California, San Diego, 184]. While the fractionation trend is interesting from a theoretical viewpoint, the near-zero Δ37Clvapor-liquid values suggest that evolved vapor-liquid samples, such as volcanic fumarolic gases and degassed glasses should faithfully preserve the δ37Cl value of the fluid responsible for magma production at depth. Even extensive Rayleigh fractionation could not change the chlorine isotope composition of a fluid by more than 0.5‰ from its original degassed value. © 2006 Elsevier B.V. All rights reserved.
Keywords: CHLORINE ISOTOPES; FLUID-PHASE SEPARATION; HYDROTHERMAL SYSTEMS; ISOTOPE FRACTIONATION